2015
DOI: 10.4238/2015.may.29.15
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of sulfate-reducing bacteria in the sediment of the Zhou Cun drinking water reservoir in Eastern China

Abstract: ABSTRACT. Sulfate-reducing bacteria (SRB) play an important role in the sediments of bay areas, estuaries, and lakes. However, information regarding the genetic diversity of SRB in the sediments of drinking water reservoirs is scarce. In this study, we collected sediment samples from different sites in the Zhou Cun drinking water reservoir between April and June 2012. To explore the genetic diversity of SRB, we used the most-probable-number (MPN) method, polymerase chain reaction denaturing gradient gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sulfides pollution is mainly concentrated in the lower water. According to the research of Yang [ 37 ], the freshwater habitat of the Zhoucun Reservoir shows a relative abundance of SRB, which is similar to the observation in marine sediments. A SRB count of approximately 4.50 × 10 4 cells/g sediment was estimated from the samples taken in 2013, which is a magnitude greater than in typical reservoirs.…”
Section: Resultsmentioning
confidence: 57%
“…Sulfides pollution is mainly concentrated in the lower water. According to the research of Yang [ 37 ], the freshwater habitat of the Zhoucun Reservoir shows a relative abundance of SRB, which is similar to the observation in marine sediments. A SRB count of approximately 4.50 × 10 4 cells/g sediment was estimated from the samples taken in 2013, which is a magnitude greater than in typical reservoirs.…”
Section: Resultsmentioning
confidence: 57%
“…The diversity and community structure of SRB and SOB have, to date, been studied using denaturing gradient gel electrophoresis (DGGE) ( Varon-Lopez et al, 2013 ; Yang et al, 2015 ), restriction fragment length polymorphism ( Luo et al, 2011 ; Reed and Martiny, 2013 ), and clone library approaches ( Yang et al, 2013 ; Purcell et al, 2014 ). However, obtaining comprehensive information about the highly diverse SRB and SOB communities, particularly SRB and SOB from the prime habitats of marine sediments, using these methods is challenging ( Aoki et al, 2015 ; Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…and Desulfobacterium sp. dominated in a study on a drinking water reservoir in Eastern China (Akpan and Iliyasu, 2015;Yang et al, 2015). Akin to the current study where abundance varied but diversity was relatively the same from one environment to the other, a study on four different environments in Mexico concluded that the distribution of SRB genera was relatively consistent across the different environment but the abundance differed.…”
Section: Microbial Influencesmentioning
confidence: 44%